Foreign Direct Investment - A Curse or A Blessing - Sandsborg,Joel; Eberhard,Johan (2014)
The purpose of this thesis is to provide the impact Foreign Direct Investment (FDI) has on economic growth and economic inequality in Sub Saharan Africa. Based on econometric estimates of 44 countries, the authors evaluate the impact on economic growth and on distribution of income in the region. A lot of the African countries hold valuable natural resources. Consequently, one would expect the countries to flourish sooner or later. Unfortunately, in many cases, this is an incorrect vision of how reality actually occurs. Multinational companies choose to locate their business in these countries and the outcome appears considerably different. We hope to contribute to the field through measuring the impact FDI has on economic growth and economic inequality depending on if the countries are relatively rich or poor in natural resources. In order to measure the involvement of the foreign investors we will use aggregated FDI net inflow as an indicator of the amount of foreign involvement. In an attempt to catch changes in economic inequality, we intend to use income distribution and for this measurement, the Gini coefficient will be used.
Keywords: Economic Growth; Economic Inequalities; Foreign Direct Investments; Sub Saharan Africa; Natural Resources